Association between nutritional literacy and nutrition label use in Chinese community residents - Yang, Ling; Cui, Yan; Du, Jing; Liu, Zihao; Duan, Ying; Qi, Qi; Liu, Huaqing; Zhang, Min (Frontiers in Nutrition, 2024)
Introduction: Nutritional literacy (NL) has a critical influence on food choices. The objective of the present study was to examine the association of NL with nutrition label use. Methods: A cross-sectional study was conducted in Bengbu, China. In total, 955 adults were interviewed using a questionnaire designed for the present study to collect information on demographics, lifestyle, nutrition label use, and NL. Binary logistic regression models were used to calculate odds ratios (OR) and 95% confidence intervals (CI) for nutrition label use and its predictive variables. Results: In total, 40.4% of the participants reported looking at nutrition label when purchasing prepackaged foods. NL was significantly positively associated with nutrition label use and specifically with checking nutrition facts table, purported nutrition benefits and purported health benefits. In terms of specific facets of NL, nutrition knowledge, applying skills, and critical skills were associated with nutrition label use. After stratification by monthly income and education, the association between NL and nutrition label use was discovered only in individuals with low monthly income. Additionally, nutrition knowledge was associated with nutrition label use only in adults with high education level, whereas applying skills were associated with nutrition label use only in those with low education level. Conclusions: The use of nutrition label remains low among Chinese community residents, especially the purported nutritional benefits and purported health benefits. NL is positively associated with nutrition label use, especially with respect to functional and critical NL, with differences based on socioeconomic status. The findings highlight the need for NL interventions targeting individuals with different levels of education and income to encourage use of nutrition label in China.